DETERMINATION OF AGRONOMIC AND QUALITY CHARACTERISTICS OF SOME SESAME (SESAMUM INDICUM L.) GENOTYPES GROWN AS A SECOND CROP IN DIYARBAKIR CONDITION - Öztürk, Ferhat (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2020)
Sesame (Sesamum indicum L.) is an important ancient annual spice and oilseed crop. widely cultivated all over the world for its seeds objectives. The experiment was conducted to determine the agronomic and quality traits of some sesame cultivars registered under second-crop in Diyarbakir condition in 2018. A total of 13 sesame genotypes (Konya, Ege (Tanas), Muganli 57. Canakkale Yenice-Pazar koyu, Vara Verde. Balikesir lvrindi, Hatipoglu, Aslanbey, Boydak, Kepsut 99. Tan 99, Strnak Kumcatt Dergul, and Ozberk-82) were used as the plant material for the study. The presented experiment was arranged in a randomized block design with three replications. In this study, plant height. the first pod height, number of branches and pods per plant, number of seeds per pod, 1000-seed weight, seed yield, oil and protein ratio, saturated-unsaturated fatty acid components were investigated. There were significant differences in seed yields of the genotypes at P<0.01 level. Seed yields varied between 1165.13-1619.66 kg ha(-1) and the highest seed yield (1619.66 kg ha(-1)) was obtained from Hatipoglu genotype. The 1000-seed weights varied between 2.6- 3.9 g with the lowest value in Konya local genotype and the highest value in Muganit-57 genotype. The greatest number of pods per plant (125.5 pods/plant) was produced from Hatipoglu genotype. Oil ratios varied between 45.91-58.03% with the maimum value in Tan 99 genotype and the lowest value in Vara verde genotype. Oleic acid contents varied between 42.12-45.41% with the highest value Hatipoglu genotype and the lowest value in Tan 99 genotype. Linoleic acid contents varied between 34.47-38.52% with the highest value in Kepsut 99 genotype and the lowest value in Muganit-57. Seed yield had significant positive correlations with 1000-seed weight and number of pods per plant. Oil contents had significant negative correlations with oleic and stearic acid contents and positive correlations with palmitic and linoleic acid contents. Accordingly, the genotype Hatipoglu performed well and showed good in seed yield and quality at all sowing times. The cultivation of that genotype in Diyarbakir Province may enrich the local production of good quality oil in Turkey.
Keywords: Sesame; Seed yield; Quality; Saturated fatty acid; Unsaturated fatty acids